2019
DOI: 10.1002/jcb.28603
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of circular RNA expression in rat dental follicle cells during osteogenic differentiation

Abstract: Circular RNAs (circRNAs) are novel noncoding RNAs and play crucial roles in various biological processes. However, little is known about the functions of circRNAs in osteogenic differentiation. The current study aimed to investigate the differential expression of circRNAs in rat dental follicle cells (rDFCs) during osteogenic differentiation, identified by RNA high-throughput sequencing and quantitative real-time polymerase chain reaction. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Many studies have confirmed that circRNAs played crucial roles in cells differentiation. Du et al demonstrated that circFgfr2 was a potential new target for bone formation, which promoted osteoblasts differentiation through regulating miR-133/BMP6 (Du et al, 2019). Li et al found that circular RNA CDR1 could regulate osteoblastic differentiation via the miR-7/GDF5/SMAD and p38 MAPK signaling pathway (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that circRNAs played crucial roles in cells differentiation. Du et al demonstrated that circFgfr2 was a potential new target for bone formation, which promoted osteoblasts differentiation through regulating miR-133/BMP6 (Du et al, 2019). Li et al found that circular RNA CDR1 could regulate osteoblastic differentiation via the miR-7/GDF5/SMAD and p38 MAPK signaling pathway (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have focussed on the role of circRNA in controlling cell differentiation, which is important in the context of periodontal regeneration and tissue engineering. Herein, we undertook a scoping review of recent research into the role of circRNA in cell differentiation in vitro and periodontal tissue healing and regeneration in vivo, drawing information from 23 studies [ 37 , 38 , 39 , 40 , 41 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Much of the existing research has focused on osteogenic differentiation of periodontal stem cells, and how circRNAs might function as a sponge for miRNAs.…”
Section: The Emerging Role Of Circrnas In Periodontal Regenerationmentioning
confidence: 99%
“…The MC3T3-E1 mouse osteoblastic cell line is commonly used to study bone formation in vitro. A total of four studies investigated the role of circRNAs in this cell line [ 66 , 67 , 68 , 69 ], rat dental follicle cells (rDFCs) [ 70 ], and gingival fibroblasts cell line [ 71 ], as shown in Table 4 .…”
Section: The Emerging Role Of Circrnas In Periodontal Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Secreted BMP6 from other cells in DF also promoted the osteogenesis via a paracrine pathway. Interestingly, BMP6 was also considered as one of the downstream targets of circular RNAs (circRNAs) in DFC differentiation, it was upregulated in circFgfr2-enhanced DFC osteogenesis [75].…”
Section: Multipotent Differentiation Of Dfcsmentioning
confidence: 99%